ANALISIS REAKSI PASAR MODAL INDONESIA PADA PERISTIWA RESHUFFLE MENTERI KABINET INDONESIA MAJU TAHUN 2020 - Muhamad Dio Alfalah; Nidya Novalia; Francisca Kristiastuti (Universitas Nurtanio Bandung, 2022)
This study aims to test the capital market's reaction to The Announcement of 2020 Indonesia Maju Cabinet's Minister Reshuffle by the President. This announcement is a political event that elicits reactions from investors in the capital market. The reaction of the capital market to the information contained in an event can be measured using the variable of trading volume activity, as well as abnormal returns. This is event study research on company shares indexed in IDX30. The observation period is 11 days. The results of the study show that there is no difference in abnormal returns and trading volume activity after the President's announcement for the 2020 Indonesia Maju Cabinet Minister Reshuffle on company shares indexed in IDX30.